Alleviation of health of the patients rehabilitated because of lower back pain - Olczak, Katarzyna; Zawirski, Marek; Heleniak, Mariusz; Niewodniczy, Maciej; Kowalczyk, Patrycja; Warchoł, Sebastian (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Background: Lumbalgia is a relevant problem of the society. Approximately among 70% of population an episode of the lumbar region of spine has been noticed. The main aim of this study is to prove the efficiency of rehabilitation in treating such ailments. Material and methods: The study included 23 patients treated in Norbert Barlicki Clinical Hospital in Lodz. For the study the patients with sciatica-like symptoms were qualified. After the series of treatments the patients were investigated using VAS scale and modified Laitinen scale. Results: After the series of treatments the pain decreased by 70,23%, the frequency of taking analgesics decreased by 68,45% and physical activity increased by 62,05%. Conclusions: The rehabilitation in patients with ailments of lumbar region of the spine in L5-S1 segment determine the alleviation of pain and improvement of physical activity among the patients.